Analysis of West Kalimantan Rubber Export Competitiveness to China - Endah Kurnia Lestari; Jessica Felita Pramono; Yulia Indrawati (Publikasi Indonesia, 2022)
Trade is the activity of exchanging goods and services between regions or countries. The purpose of this research is to help the needs of the community by encouraging economic growth. Increasing exports has an important role for the survival of the country. West Kalimantan also experienced problems in the trade sector that occurred in 2014. In 2014 West Kalimantan's exports decreased to 51.65 percent from 2013. The analytical methods used were RCA, RSCA, ISP, ECI, EPD, CEP and CMS. The result of research based on RCA analysis is 29.48 which means it has competitiveness and comparative advantage. Based on the RSCA analysis, 0.88 means that it has competitiveness and comparative advantage. Based on the ISP analysis of 0.91 which means that West Kalimantan is an exporting country, the ECI analysis produces a value of 1.92 which means that West Kalimantan has.